KONSEP DASAR SUPERVISI PENDIDIKAN - Arief Dwi Kurniawan; Ali Muhdi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research aims to examine the basic concepts of educational supervision, its functions and approaches, and the principles that support its effective and professional implementation. The paper was written using library research through analysis of various relevant scientific sources. The results of the study indicate that educational supervision is a professional service oriented towards improving the quality of learning and developing teacher competencies through a humanistic, collaborative, and data-driven approach. Philosophically, supervision has shifted from a power-over paradigm to a power-with paradigm, which positions teachers as partners in the development process. Supervision also has research, assessment, improvement, and development functions using various approaches, such as directive, collaborative, non-directive, and clinical. To be effective, supervision must be implemented based on scientific, democratic, cooperative, constructive, creative, practical, and comprehensive principles. Thus, educational supervision is expected to enhance teacher professionalism and create a quality and sustainable educational environment.